Astaxanthin-Producing Microalgae Identification Using 18S rRNA : Isolates from Bangkalan Mangrove Waters and Sowan Tuban Northern Waters, East Java, Indonesia - Dini Ermavitalini; Siska Yulia Rukhmana; Thalita Meidina; Leonardo Pascalis Dimas Cahyo Baskoro; Triono Bagus Saputro; Ni’matuzahroh Ni’matuzahroh; Hery Purnobasuki (Journal of Tropical Biodiversity and Biotechnology, 2021)
Microalgae are a group of micro-sized photosynthetic organisms that range from prokaryotic cyanobacteria to eukaryotic algae. Microalgae are widely used as a source  of natural food, cosmetic ingredients, food ingredients, and a source of pigments. This study aims to identify species of four microalgae isolates named B1, B2, B3, and S2 from Bangkalan Mangrove Waters and Sowan Tuban Northern Waters, and to determine their astaxanthin pigment concentration under 1 M NaCl. Species identification was carried out through a molecular approach by utilization of an 18S rRNA gene marker. A quantitative test of astaxanthin concentration was carried out by spectrophotometric analysis. Molecular identification results show that isolates B1 and B3 are closely related to Chlorella sp., while isolates B2 and S2  are closely related to Picochlorum maculatum. Moreover, under salinity stress condition of 1 M NaCl shown a significant decrement of astaxanthin production compared to the control treatment. At 1 M NaCl, the astaxanthin content of isolate B1 was 4x10-5 mgL-1, isolate B2 was 2x10-5 mgL-1, isolate B3 was 1x10-5 mgL-1, and isolate S2 was 6x10-6 mgL-1. All in all, isolate S2 has the highest astaxanthin among the other isolates at normal conditions, while under salt stress regime, isolate B1 shown to be the best source for astaxanthin.